THE DILLEM OF THE RIGHT TO PRIVACY IN INDONESIA: DOES INDONESIA’S CORRUPTION ERADICATION COMMISSION (KPK) IN SPYING PEOPLE VIOLATE INTERNATIONAL HUMAN RIGHTS LAWS TO PROTECT THE RIGHT TO PRIVACY? - Wijaya, Dodik Pranata (Faculty of Law Universitas Trunojoyo Madura, 2019)
Corruption is a serious crime in Indonesia. Indonesia commonly recognize that Corruption as extra ordinary crime that has to be combated by extra ordinary means as well. Interception has been determined as the best way to reduce the number of these engaged in corruption, Indonesia is adherence to some international human rights instrument aims to support the basic rights of the people. The scope of the concept of privacy, in some theorists’ perspective has sailed to be properly conceptualized. In addition, the international community recognizes privacy is a fundamental human right which is well-described in several Conventions. This reflects the importance of the right to privacy for every individual in the world, either for adult, children or for people who have disabilities. Some of the interception actions done by the KPK, do not comply with the international principles on human rights in electronic surveillance actions. This means Indonesia must improve its laws through adding some articles in order to fully comply with international principles on human rights in electronic surveillance actions. The research method used is normative juridical, normative juridical is research based on the analysis of legal materials in the form of several legal principles and several legal theories as well as laws and regulations that are in accordance with the problems in this study.